Private Equity and Venture Capital Investment Attractiveness - Dahlman,Samuel; Esphabodi,Kimiya (2023)
This paper is a cross-country study on how national culture affects institutional private equity and venture capital investments in Europe and is based on the previous works of Groh, Liechtenstein and Lieser (2010) and Hofstede, Hofstede and Minkov (2011). We argue that national culture affects capital allocation and that this parameter is often missing in the contemporary discourse on the drivers of investments. This thesis thus aims to further explain what makes some countries more attractive for institutional investors than others by combining formal and informal institutions in a way that no previous study has done. Our hypotheses test the effects that formal institutions and the cultural traits of power distance, uncertainty avoidance, masculinity and individualism have on private equity and venture capital funding in Europe 2021. Additionally, we hypothesize that the effects of these differ depending on country development level, hence the countries are grouped and studied separately. To test the hypotheses, we use linear regression analysis for 33 European countries by using 767 data points from 2015–2020. Our findings indicate that more developed countries attract more capital during recession because of higher quality formal institutions. As these countries grow more attractive relative to the rest of Europe, they attract funds at a higher rate compared to less developed countries. Furthermore, less developed countries that are more individualistic tend to raise higher volumes of funds, and certain cultural traits could potentially have a greater impact on capital allocation in less developed countries when compared to more developed ones. Thus, both formal and informal institutions can explain why some European countries are more attractive for investment than others.